Evidence of Sex Differentiation Based on Morphological Traits During the Early Development Stage of Mud Crab Scylla paramamosain - Cui, Wenxiao; Fang, Shaobin; Lv, Ligang; Huang, Zhi; Lin, Fei; Wu, Qingyang; Zheng, Huaiping; Li, Shengkang; Zhang, Yueling; Ikhwanuddin, Mhd; Ma, Hongyu (Frontiers in Veterinary Science, 2021)
In order to uncover the sexual difference in morphology and how early they appear during the development stage of mud crab Scylla paramamosain, we measured, observed, and biostatistically analyzed morphological traits related to sex. For unveiling the morphological differences between sexes, morphological traits involving abdomen width (AW), carapace length (CL), and carapace width (CW), were first measured during the crablet development stage of the S. paramamosain in the present study. The correlation analyses and path analyses exhibited that sexual dimorphism in third abdomen width (AW3) and fourth abdomen width (AW4) could be used for sex identification from stage C Ⅵ (stage Ⅵ of crablet). Based on the stepwise discriminant analysis and standardized traits, a sex discriminant equation was constructed, which is capable for sex identification in crablets from stage C Ⅵ. Observations for secondary sexual traits and abdomen morphology (shape and pleopods) using a dissecting microscope or scanning electron microscope indicated that sexes are easily identified at stage C Ⅷ according to the abdomen shape, meanwhile, at stage C Ⅱ based on pleopods difference, and at stage C Ⅰ by the presence or absence of gonopores. The findings in this study contribute greatly to the accuracy of sex identification of the S. paramamosain during the early development stage, which promotes the understanding of the morphological differentiation mechanism of sex.